Human Anatomy - Saladin, Kenneth S.; York, Justin J. (New York : Mc Graw Hill, LLC., 2024)
"Saladin's Human Anatomy goes beyond descriptions of body structure to read as a story that weaves together basic science, clinical applications, the history of medicine, and the evolutionary basis of human structure. Saladin combines this humanistic perspective with vibrant photos and art to convey the beauty and excitement of the subject to beginning students. Changes to the Sixth Edition Attending scientific conferences, subscribing to several scientific and medical journals, and engaging in online forums and answering public questions on anatomy, physiology, and health help Ken Saladin stay abreast of advances in the field. In this edition, he introduces newly discovered functions of osteocytes, astrocytes, dendritic cells, the greater omentum, the corneal epithelium, and even eyelashes. He reports new research insights on peroxisome production, tracing white matter tracts of the brain, and endocrine disruptors; new discoveries of cerebral lymphatics, and pulmonary production of blood platelets; and clinical advances in asthma and cancer mortality and survival, cord blood transplants, stem-cell harvesting, and regenerative medicine. These and more examples are listed chapter by chapter later in this section"
Includes appendices, glossary, and index.
Keywords: Human anatomy